Crystallization and surface Morphology following annealing using ZnO thin film: Investigating the impact of annealing on crystallization and surface morphology of ZnO thin films (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The glass substrates had ZnO thin films produced on them using a sol-gel dip coatingprocess. All sorts of temperatures, from 350 to 550 degrees Celsius, were used to anneal the films. Theimpact of annealing temperature on the films' structural and morphological features was studied usingX-ray diffraction (XRD) and atomic force microscopy (AFM). Different processing conditions are usedduring manufacturing, all of which might alter the final attributes of a device based on amorphousoxides. Although zinc oxide shows promise as a transparent amorphous oxide, its structure is sensitiveto temperature changes. Here, we looked at the phenomenon of surface recrystallization in amorphouszinc oxide layers produced by pulsed laser deposition onto fused silica, sapphire, and Si substrates.Extremely out-of-equilibrium phase structures were found in the three-layer preparation. All thedeveloped ZnO films display strongly (0001)-oriented patterns without in-plane rotation, as evidenced byin situ reflection high-energy electron diffraction (RHEED) and ex situ X-ray diffraction (XRD). Asevidenced by atomic force microscopy (AFM) pictures, “ridge-like” and “particle-like” surfacemorphologies are found for the ZnO films formed in a molecular O2 environment with and without aninitial deposition of Zn adatoms, respectively, before ZnO development with oxygen plasma. The ultimatesurface shape and optical characteristics of the ZnO film are significantly affected by this artificiallyconstructed interfacial layer.